Review of The Routledge Companion to Masculinity in American Literature and CultureReview of Routledge Companion to Masculinity in American Literature and Culture - Saidi, Amira Rihab (AMERICANA E-journal of American Studies in Hungary, 2022)
The Routledge Companion to Masculinity in American Literature and Culture Lydia R. Cooper (editor) New York, Routledge, 2022 425 pages ISBN: 978-0-367-52008-3 (hbk) ISBN: 978-1-032-15662-0 (pbk) ISBN: 978-0-367-52009-0 (ebk) DOI: 10.4324/9780367520090